Our green and living world - Edward S. (London, 1984)
The authors survey the ways in which we are losing our ability to survive biologically and present new approaches to regaining it. They examine our planet's green life-layer from every point of view: cultural and artistic, religious, ecological, economic, and scientific. These world respected botanists highlight the true worth of the Plant Kingdom for our lives - from Amazonian rain forests to African violets or tropical foliage plants at the windowsill. India and other lands help provide us with a remarkable arsenal of plant-derived medicines that cure leukemia and other malignancies, that control hypertension, and that also prevent the body from rejecting transplanted organs. Mexico, for instance, produces the wild yams that provide chemical raw materials for the contraceptive pill. And in Kenya, we meet a young wife who brings her to a respected dispenser of traditional medicines extracted from jungle greenery.
Keywords: Nature conservation